Signal Degradation and Excess Insertion Loss of Optical Mach–Zehnder Modulators in the Presence of Electronic Dispersion Compensation - Xiatao Huang; Xingwen Yi; Mingyue Zhu; Jing Zhang; Zengjie Zhang; Yang Song; Kun Qiu (IEEE Photonics Journal, 2017)
Mach–Zehnder (MZ) modulators are widely used in optical transmitters to generate high-speed optical signals. With electronic dispersion compensation (EDC), the driving signals to MZ modulators change from digital to analog, or continuous waveforms. Consequently, there is signal degradation from their sinusoidal transfer curves. In this paper, we theoretically and numerically investigate the signal degradation in optical transmitters using MZ modulators in the presence of EDC. We show that the temporal waveforms follow the Gaussian distribution when the EDC is large, and therefore, the modulation index needs to be optimized between the output SNR and the excess insertion loss of MZ modulators. With varying modulation index, we quantify the output SNR and excess insertion loss of optical IQ modulators that consist of two parallel MZ modulators. The calculations are also extended to the scenarios where the sinusoidal transfer curves are compensated for. All the analytical results are verified in a simulation of QPSK transmissions, and they are useful for finding an optimized modulation index for a tradeoff between the output SNR and excess insertion loss.